Effect of modified trampoline use on balance and lower body strength in untrained individuals - Tay, Zhong Ming (2017)
BACKGROUND- In the recent years, there was a huge increase in number of trampoline parks found in Singapore. Trampolines has been widely made accessible for public use to improve physical fitness level. PURPOSE- This study investigated the effects of a 6 weeks’ trampoline training programme (TT) on lower leg strength and balance in comparison to a traditional resistance training programme (RT) of the same duration. We hypothesized that TT will give the same amount of increase in strength and balance compared to RT. METHODS- 28 subjects untrained in resistance or trampoline training performed either resistance training or trampoline based training for 30 min a session, 2 times a week with at least 48 hours of rest in between sessions. Out of the 28 subjects recruited, 2 has dropped out due to an unrelated injury and non-fulfillment of training requirement respectively. The remaining 26 completed an assessment for static and dynamic balance as well as peak knee torque production before (Pre) and after the programme (Post). RESULTS- Dynamic balance and peak knee torque production showed significant interaction with time while static balance does not show any significant interaction. There was no significant main effect of training type or interaction between training type and condition for all three variables. CONCLUSION- There is a significant positive effect of TT on dynamic balance and lower body strength as compared to a traditional RT of the same duration. Thus, it may be used as an alternative to traditional RT.